(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Language learning is a complex process that involves not only acquiring vocabulary and grammar but also developing self-regulated learning habits. Metacognition, or the awareness and control of one’s own learning processes, is a key factor in academic success, especially in second language acquisition. This study investigates the connection between metacognitive awareness and the application of language learning strategies (LLSs). Based on learner surveys, existing theoretical frameworks, and real-life classroom examples, the findings indicate that learners with high metacognitive skills tend to use strategies more effectively, leading to improved performance. The paper concludes with pedagogical recommendations for fostering metacognitive skills among language learners.